Spatial access to health care in Costa Rica and its equity: a GIS-based study - Rosero Bixby, Luis (2004)
This study assembles a geographic information system (GIS) to relate the 2000 census population (demand) with an inventory of health facilities (supply). It assesses the equity in access to health care by Costa Ricans and the impact on it by the ongoing reform of the health sector. It uses traditional measurements of access based on the distance to the closest facility and proposes a more comprehensive index of accessibility that results from the aggregation of all facilities weighted by their size, proximity, and characteristics of both the population and the facility. The weighting factors of this index were determined with an econometric analysis of clinic choice in a national household sample. Half Costa Ricans reside less than 1 km away from an outpatient care outlet and 5 km away from a hospital. In equity terms, 12–14% of population are underserved according to three indicators:having an outpatient outlet within 4 km, a hospital within 25 km, and less than 0.2 MD yearly hours per person. The data show substantial improvements in access (and equity) to outpatient care between 1994 and 2000. These improvements are linked to the health sector reform implemented since 1995. The share of the population whose access to outpatient health care (density indicator) was inequitable declined from 30% to 22% in pioneering areas where reform began in 1995–96. By contrast, in areas where reform has not occurred by 2001, the proportion underserved has slightly increased from 7% to 9%. Similar results come from a simpler index based on the distance to the nearest facility. Access to hospital care has held steady in this period. The reform achieved this result by targeting the least privileged population first, and by including such measures as new community medical offices and Basic Teams for Integrated Health Care (EBAIS) to work with these populations. The GIS platform developed for this study allows pinpointing communities with inadequate access to health care, where interventions to improve access would have the greatest impact.